Theban Harbours and Waterscapes Survey, 2015*. Issue 1 (January 2015) - Graham, Angus; Strutt, Kristian D.; Toonen, Willem H. J.; Pennington, Benjamin T.; Löwenborg, Daniel; Masson-Berghoff, Aurélia; Emery, Virginia L.; Barker, Dominic S.; Hunter, Morag A.; Lindholm, Karl-Johan; Johansson, Carolin
Report on the 2015 season of the Theban Harbours and Waterscapes Survey (THaWS). The paper discusses the extension of geoarchaeological and geophysical investigations to the east of the Ramesseum, the continuing work in and around the Temple of Millions of Years of Amenhotep III, and the topographic survey and geophysical survey of the western mounds of the Birket Habu.